2016
DOI: 10.1177/1471301214564792
|View full text |Cite
|
Sign up to set email alerts
|

The positive aspects of caregiving in dementia: A critical review of the qualitative literature

Abstract: Copyright © and Moral Rights are retained by the author(s) and/ or other copyright owners. This copy may differ from the final published version. A copy can be downloaded for personal non-commercial research or study, without prior permission or charge. This item cannot be reproduced or quoted extensively from without first obtaining permission in writing from the copyright holder(s). The content must not be changed in any way or sold commercially in any format or medium without the formal permission of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
234
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(270 citation statements)
references
References 51 publications
(215 reference statements)
16
234
1
9
Order By: Relevance
“…One example of this is the recommendations for interpretation of the frequently used Zarit Burden Interview [34]. However, the results of our study indicate that burdens and benefits are two different constructs, as presumed by Lloyd, Patterson and Muers [33]. The non-significant correlations between the BSFC-s with the ADL and IADL caregiving items also confirmed our hypotheses about the discriminant validity of the BSFC-s.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One example of this is the recommendations for interpretation of the frequently used Zarit Burden Interview [34]. However, the results of our study indicate that burdens and benefits are two different constructs, as presumed by Lloyd, Patterson and Muers [33]. The non-significant correlations between the BSFC-s with the ADL and IADL caregiving items also confirmed our hypotheses about the discriminant validity of the BSFC-s.…”
Section: Discussionsupporting
confidence: 81%
“…It is important to take into consideration that to date, the benefits arising from the care situation and the burden on the informal CGs have been viewed as two ends of one continuum [33]. One example of this is the recommendations for interpretation of the frequently used Zarit Burden Interview [34].…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study of caregivers of seniors with chronic conditions identified both barriers and facilitators of resilience, with caregivers’ sense of control, mastery, and support (or lack thereof) playing a role in both categories [40]. Importantly, many caregivers report positive changes or growth due to caregiving, even while reporting high levels of burden [13]. Helping caregiver to bolster their internal resources, or leverage their existing strengths, may improve resilience or benefit finding, or otherwise mitigate some of the potentially deleterious effects of caregiving stress.…”
Section: Discussionmentioning
confidence: 99%
“…While many caregivers find benefits in the experience, such as a sense of purpose [1; 2], many also report feeling stressed or burdened by their role [3]. Moreover, some caregivers experience serious problems like depression [4].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing PAC is important because many caregivers report deriving meaning or purpose from caregiving in ways that may ameliorate or compensate for the negative aspects of the experience, may help identify caregivers with low risk for negative outcomes, and may support the implementation of clinical interventions (Carbonneau et al, 2010;Connell et al, 2001;Farran et al, 1999;Liu & Gallagher-Thompson, 2009;Lloyd et al, 2014;Schulze & Rossler, 2005;Rapp & Chao, 2000). Some measures of PAC such as the Positive Aspects of Caregiving (Tarlow et al, 2004) and the Gain in Alzheimer care INstrument (GAIN; Yap et al, 2010), were designed specifically to assess PAC in dementia carers and may not fully capture the experience of other caregivers (i.e., carers of those with chronic physical illness; Lloyd et al, 2014).…”
mentioning
confidence: 99%